Kualitas Kepribadian Pekerja (santri): Etos Kerja dan Disiplin Kerja dan Pengaruhnya terhadap Iltizam Bil Jamaah - Mochamad Noval Nasrudin (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the work ethic and work discipline variables on Iltizam bil Jama'ah. This research is explanatory (explaining) is